PENGUATAN MENTAL HEALTH GEN Z UNTUK MENCEGAH DAN MENANGGULANGI ECO-ANXIETY - Tundjung Herning Sitabuana; Rieven Yehezkiel Nasari; Yonikken Gautami Pundarika; Dixon Sanjaya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2026)
Mental health issues are experiencing a significant upward trend among adolescents (Gen Z). Minister of Health stated that 1 in 10 Gen Z members experience mental health disorders. Data from Indonesia Nation Adolescent Mental Health Survey (I-NAMHS) states that 1 in 20 Gen Z. One of these mental health disorders is eco-anxiety. Eco-anxiety has become a phenomenon in many countries such as the UK, Brazil, and Philippines. Eco-anxiety phenomenon is further exacerbated by its spread through social media with doomscrolling techniques. Therefore, it is necessary to strengthen mental health among Gen Z to provide awareness about eco-anxiety so that they can build resilience against current ecological crisis. Social Service team from Untar Faculty of Law (PKM team) will conduct a socialization activity with topic